ChemInform Abstract: Expanded Scope of the Asymmetric Hydrogenation of Minimally Functionalized Olefins Catalyzed by Iridium Complexes with Phosphite—Thiazoline Ligands. Issue 1 (7th January 2014) - Mazuela, Javier; Pamies, Oscar; Dieguez, Montserrat
Abstract A new structurally important class of Ir‐phosphite‐thiazoline precatalysts is developed to be used in the hydrogenation reaction of the challenging substrates like minimally functionalized 1, 1‐disubstituted terminal olefins, (E)‐trisubstituted olefins, α, β‐unsaturated ketones and esters.